ANALYSE DE LA PERFORMANCE FINANCIERE DE LA SOCIETE « PLANTATIONS ET HUILERIES DU CONGO » (PHC) de 2003 à 2007 - Pierre, LOMATA MELENGE Jean-; NGUTU BASEKAWIKE Philomène, (IJRDO - Journal of Business Management, 2021)
Our research focused on the analysis of the financial performance of the formercompany "Plantations et Huileries du Congo", PHC in acronym, for a period of five years, from2003 to 2007. Our objective is to verify whether the financial health of the Company PHC washealthy five years after the two wars of liberation and to identify the underlying reasons that ledour company under study to sell all its plants and abandon palm oil production.Through the financial analysis of PHC's financial statements from 2003 to 2007, ananalysis conducted in two forms including arithmetic analysis of balance sheet items and the useof ratios, we confirmed our hypothesis that PHC experienced financial underperformance fiveyears after the two wars in Congo. The company experienced a financial imbalance and itsinvested capital was not profitable. This is the fundamental reason why in September 2009 theUnilever Group decided to give up palm oil production and to sell all its plants and plantations to asubsidiary (Feronia) of the Canadian company Trinorth